Living literacies literacy for social change - Pahl, Kate 1962-; Rowsell, Jennifer 1969- (The MIT Press, 2020)
"Pahl and Rowsell combines newer orientations in literacy studies - co-production, new materialism, post-humanism, digital and maker epistemologies - to describe a living, enacted model of literacy"--
Bevorzugte Informationsquelle: Landingpage (MIT Press Direct), da weder Titelblatt noch Impressum vorhanden
Keywords: EDUCATION/Literacies; SOCIAL SCIENCES/Anthropology & Archaeology; EDUCATION/General; Literacy / Social aspects; Literacy / Research; Critical pedagogy